Pengaruh Permainan Tradisional Pat Ni Gajah Terhadap Motorik Kasar Anak Usia 5-6 Tahun Di TK Mandiri ABCD Kecamatan Sipoholon - Kartika Pakpahan; Hisardo Sitorus; Emmi Silvia Herlina (Universitas Katolik Widya Karya Malang, 2023)
Based on the results of the initial study conducted at the Mandiri ABCD Kindergarten, Sipoholon District, there were several problems with the Pat Ni Gajah game, namely the lack of gross motor skills in children when playing, and children still lacking in developing body movements, but through playing activities, children can develop agility and balance as well as eye and eye coordination. foot. Some children also lack the natural ability to maintain balance when trying to play the Pat Ni Gajah game. The aim of this research was to determine the effect of the traditional game Pat Ni Gajah on the gross motor skills of children aged 5-6 years at the Mandiri ABCD Kindergarten, Sipoholon District. The method used in this research is an inferential quantitative research method. The population is all children aged 5-6 years in Mandiri ABCD Kindergarten, Sipoholon District, 2022/2023 Academic Year, totaling 101 people and a sample of 40 children was determined using random sampling techniques. Data was collected with 19 positive closed questionnaire items. The results of the data analysis show that there is an influence of the traditional Pat Ni Gajah game on the gross motor skills of children aged 5-6 years in the Mandiri ABCD Kindergarten, Sipoholon District: 1) Test the analysis requirements: a) positive relationship test obtained by the value rxy = 0.552 > rtable(a= 0.05,n=40) = 0.312, thus it is known that there is a positive relationship between variable =38)= 2.021, thus there is a significant relationship between variable .63